2012
DOI: 10.1158/0008-5472.sabcs12-p5-14-06
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P5-14-06: Analysis of test-therapy concordance for biomarkers uPA and PAI-1 in primary breast cancer in clinical hospital routine: Results of a prospective multi-center study at Certified Breast Cancers in Germany

Abstract: Objective: Biomarkers uPA and PAI-1 are guideline recommended by ASCO, USA, and AGO, Germany, to be used in primary breast cancer to avoid unnecessary CTX in medium risk recurrence patients [G2, N−, HR+, Her2neu−, >35 years]. For quality assurance of uPA/PAI-1 testing an analysis of test-therapy concordance was performed. Methods: Prospective, non-interventional, multi-center study over two years among six Certified Breast Centers in Germany to analyze application of uPA/PAI-1 and use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2013
2013
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…Hierbei wurden die Kosten des Tests gegenüber den gewonnenen QALYs (qualitätsadjustierte Lebensjahre) und den Kosten für die eingesparten Therapien verglichen. Die kalkulierten Kosten lagen bei 8023 $ pro gewonnenem QALY (im amerikanischen Gesundheitswesen wer-In a prospective, multicentre trial, the use of the test in 93 patients helped to avoid 35 therapies or, respectively, for 210 cycles 12.1 years of chemotherapy application time [68]. In addition, costs of 221 816 € for systemic therapy, 25 749 € for GCS-F, and 34 353 $ for further accompanying therapies were saved (in total 281 918 $).…”
Section: Gesundheitsökonomie Und Versorgungsforschungunclassified
See 1 more Smart Citation
“…Hierbei wurden die Kosten des Tests gegenüber den gewonnenen QALYs (qualitätsadjustierte Lebensjahre) und den Kosten für die eingesparten Therapien verglichen. Die kalkulierten Kosten lagen bei 8023 $ pro gewonnenem QALY (im amerikanischen Gesundheitswesen wer-In a prospective, multicentre trial, the use of the test in 93 patients helped to avoid 35 therapies or, respectively, for 210 cycles 12.1 years of chemotherapy application time [68]. In addition, costs of 221 816 € for systemic therapy, 25 749 € for GCS-F, and 34 353 $ for further accompanying therapies were saved (in total 281 918 $).…”
Section: Gesundheitsökonomie Und Versorgungsforschungunclassified
“…In einer prospektiven, multizentrischen Studie konnten durch den Einsatz des Tests bei 93 Patientinnen 35 Therapien bzw. bei 210 Zyklen 12,1 Jahre Chemotherapieapplikationszeit vermieden werden [68]. Es wurden zudem Kosten von 221 816 € für Systemtherapien, 25 749 € für GCS-F, und 34 353 $ für weitere Begleittherapien eingespart (gesamt 281 918 $).…”
unclassified
“…Testing for the biomarkers uPA and PAI can be done to avoid unnecessary chemotherapy in patients with primary breast cancer classified as medium risk (G2, N−, HR+, HER2/neu−, > 35 years). A prospective, multi-centre study found that use of these biomarkers in 93 patients prevented 35 chemotherapies or 12.1 years of chemotherapy application (calculation based on 210 cycles) [14]. Costs of € 221 816 for systemic therapy, € 25 749 for GCS-F and $ 34 353 for additional supportive therapies were saved (total savings: $ 281 918).…”
Section: Tests For Adjuvant Systemic Therapiesmentioning
confidence: 99%